What rights matter? Examining the place of social rights in the EU's artificial intelligence policy debate - Jędrzej Niklas; Lina Dencik (Internet Policy Review, 2021)
References to "European values" are often rooted in some perception of a commitment to particular rights that uphold certain principles about democracy and the relationship between state, market and citizens. Whilst rarely translated into consistent policy frameworks or activities, the formulation of new policy areas, such as artificial intelligence (AI), provide a window into what priorities, interests and concerns currently shape the European project. In this paper, we explore these questions in relation to the recent AI policy debate in the European Union with a particular focus on the place of social rights as a historically pertinent but neglected aspect of policy debates on technology. By examining submissions to the recent public consultation on the White Paper on AI Strategy, we argue that social rights occupy a marginal position in EU's policy debates on emerging technologies in favour of human rights issues such as individual privacy and non-discrimination that are often translated into design solutions or procedural safeguards and a commitment to market creation. This is important as systems such as AI are playing an increasingly important role for questions of redistribution and economic inequality that relate to social rights. As such, the AI policy debate both exposes and advances new normative conflicts over the meaning of rights as a central component of any attachment to "European values".
Keywords: 300; Social rights; Artificial intelligence; European Union; European values; Datafication